Electrically evoked itch in human subjects - Solinski, Hans Jürgen; Rukwied, Roman (Frontiers in medicine, 2021)
Administration of chemicals (pruritogens) into the skin evokes itch based on signal transduction mechanisms that generate action potentials mainly in mechanically sensitive and insensitive primary afferent C-fibers (pruriceptors). These signals from peripheral neurons are processed in spinal and supra-spinal centers of the central nervous system and finally generate the sensation of itch. Compared to chemical stimulation, electrical activation of pruriceptors would allow for better temporal control and thereby a more direct functional assessment of their activation. Here, we review the electrical stimulation paradigms which were used to evoke itch in humans in the past. We further evaluate recent attempts to explore electrically induced itch in atopic dermatitis patients. Possible mechanisms underlying successful pruritus generation in chronic itch patients by transdermal slowly depolarizing electrical stimulation are discussed.
Gesehen am 09.02.2021